Advances in teaching and learning on facebook in higher institutions - Haruna, Chiroma; Mohd Shuib, Nor Liyana; Abubakar, Adamu; Zeki, Akram M.; Gital, Abdulsalam Ya’u; Herawan, Tutut; Jemal, Abawaje (Institute of Electrical and Electronics Engineers Inc., 2017)
Facebook has now become the most popular and extensively used social networking site among students of institutions of higher education. This makes it a widespread tool for communication and exchange of ideas. Notable to that is an active research in determining the utility of Facebook as a complementary tool in teaching and learning. The uses of the social networking sites especially, Facebook has been reported in a wide variety of results with respect to factors, such as students' learning performance, involvement, and acceptance, have been reported in the literature. This paper presents a comprehensive review of recent studies that employ Facebook as a tool for teaching and learning in institutions of higher education. We analyze the use of Facebook as a teaching and learning tool for various courses. Thereafter, its impacts on enhancing student learning outcomes as well as its negative impact on students' performance are evaluated. We also highlight the main limitations of the existing and previous studies. Future research directions for incorporating Facebook into the teaching and learning at institutions of higher education are suggested. This review is helpful to educators who plan to integrate Facebook into their teaching as well as to the researchers for further exploration of Facebook as a tool in teaching and learning.